Rethingking Pendidikan Islam Antiradikal dan Kejahatan Siber Melalui Program Benchmarking Literasi - Rizki, Azrul; Iqbal, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2020)
Through rethingking and civilizing digital soft literacy (pesantren), pesantren are believed to be able to unravel the symptoms of religious radicalism and cyber crime in an increasingly strong virtual space. Literacy benchmarking program is able to parse the symptoms of religious radicalism and cyber crime in virtual space through (1) the habituation stage through reading non-learning books for 15 minutes before learning begins; (2) the development stage includes literacy olympics, peaceful literacy and sharing, literacy creations, silent literacy, social literacy, literacy actions, literacy exhibitions, literacy corners, literacy contributions, literacy discussions, and literacy awards; learning phase, namely the stage to understand the term